GROUND-PENETRATING RADAR AND ITS USE IN SEDIMENTOLOGY: PRINCIPLES, PROBLEMS AND PROGRESS - Neal A. (My University, 2004)
Ground-penetrating radar (GPR, also referred to as ground-probing radar, surface-penetrating radar, subsurface radar, georadar or impulse radar) is a noninvasive geophysical technique that detects electrical discontinuities in the shallow subsurface (<50 m). It does this by generation, transmission, propagation, reflection and reception of discrete pulses of high-frequency (MHz) electromagnetic energy. During the 1980s radar systems became commercially available, but it was not until the mid-1990s that sedimentary geologists and others began to widely exploit the technique. During the last decade numerous sedimentological studies have used GPR to reconstruct past depositional environments and the nature of sedimentary processes in a variety of environmental settings; to aid hydrogeological investigations, including groundwater reservoir characterisation, and to assist in hydrocarbon reservoir analogue studies. This is because in correctly processed radar profiles, and at the resolution of a survey, primary reflections usually parallel primary depositional structure. Despite the wide use of GPR, a number of fundamental problems remain in its application to sedimentary research. In particular, there are a wide range of approaches to the processing of radar data and interpretation techniques used on the final subsurface images vary widely, with little consensus over a common methodology. This review attempts to illustrate that methods for the collection, processing and interpretation of radar data are intimately linked and that thorough understanding of the nature, limitations and implications of each step is required if realistic sedimentological data are to be generated. In order to extract the maximum amount of meaningful information, the user must understand the scientific principles that underlie the technique, the effects of the data collection regime employed, the implications of the technique's finite resolution and depth of penetration, the nature and causes of reflections unrelated to primary sedimentary structure, and the appropriateness of each processing step with respect to the overall aim of the study. Following suitable processing, a radar stratigraphy approach to reflection profile interpretation should be adopted. New or modified terminologies and techniques to define a radar stratigraphy are also recommended, in order to make the interpretation process more transparent and to avoid confusion with related methodologies such as seismic stratigraphy and sequence stratigraphy. The full potential of GPR in sedimentary research will only be realised if more thorough and systematic approaches to data collection, processing and interpretation are adopted.